2016
DOI: 10.1002/arp.1536
|View full text |Cite
|
Sign up to set email alerts
|

Colour to Greyscale Pixels: Re‐seeing Greyscale Archived Aerial Photographs and Declassified Satellite CORONA Images Based on Image Fusion Techniques

Abstract: To date, archived aerial photographs or recently declassified satellite CORONA images have been used to support archaeological research. However the use of such images is limited to the interpretation of greyscale images, which can be improved by image analysis processes including filters, edge detection techniques, etc. This article presents a methodology to improve the interpretation of these images by adding colour from recently acquired satellites or airborne sensors. The methodology followed in this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…However, the fusion and integration of data gathered from different sensors is quite challenging. Although some fusion techniques already exist, like pan-sharpening between multi-spectral and panchromatic bands of the same or different satellite sensors [26,27], or as more recently shown, fusion between archive greyscale and recent multispectral satellite images [28], fusion methodologies of more diverse datasets need to be developed and tested for archaeological research. Studies have shown that it is feasible to scale-up ground spectroradiometric data (i.e., ground spectral signatures) to existing [29] or even forthcoming satellite sensors [30].…”
Section: Methodsologymentioning
confidence: 99%
“…However, the fusion and integration of data gathered from different sensors is quite challenging. Although some fusion techniques already exist, like pan-sharpening between multi-spectral and panchromatic bands of the same or different satellite sensors [26,27], or as more recently shown, fusion between archive greyscale and recent multispectral satellite images [28], fusion methodologies of more diverse datasets need to be developed and tested for archaeological research. Studies have shown that it is feasible to scale-up ground spectroradiometric data (i.e., ground spectral signatures) to existing [29] or even forthcoming satellite sensors [30].…”
Section: Methodsologymentioning
confidence: 99%
“…To detect and map potential traces of the remains, archive and recent aerial photographs have been used. Towards this end, identification of potential crop and soil marks [7], which are considered as a proxy for buried archaeological remains was studied. Based on pan-sharpening techniques these marks could be enhanced and identified from recent orthophotos (see [7]).…”
Section: B Semi Macro-scale Levelmentioning
confidence: 99%
“…Towards this end, identification of potential crop and soil marks [7], which are considered as a proxy for buried archaeological remains was studied. Based on pan-sharpening techniques these marks could be enhanced and identified from recent orthophotos (see [7]). Several marks were also identified after photo-interpretation and in situ inspections, using Global Navigation Satellite Systems (GNSS).…”
Section: B Semi Macro-scale Levelmentioning
confidence: 99%
“…However, in other aerial images, interpretation can be problematic due to the noise of the datasets. It has been demonstrated in [17] that such datasets might be fused together using pan-sharpening techniques in order to retrieve the lost archaeological marks and therefore assist archaeologists for better understanding a site. Other aerial images taken during the 70's are also available from the Department of Land and Surveyors.…”
Section: Archivmentioning
confidence: 99%
“…CORONA images have been used in other areas in order to support archaeological research [20]. Some first studies from the potential use of CORONA images for archaeological research in Cyprus can be found in [17] although it should be mentioned that the quality of the images over Cyprus is relative poor (low SNR) compare to other areas of the world. CORONA were acquired at different spatial resolution, acquisition modes such as stereo etc.…”
Section: Satellite Imagesmentioning
confidence: 99%